Hubungan Motivasi Belajar dengan Minat Berwirausaha Siswa Kelas XI Tata Kecantikan SMK Negeri 3 Payakumbuh - Azzahra, Dinda fahrani; Hayatunnufus (Universitas Negeri Jakarta, 2024)
This study aims to analyze learning motivation, entrepreneurial interest, and the relationship between these two factors among class XI beauty students of SMK 3 Payakumbuh. This study uses descriptive association with a quantitative approach. The population is the class XI beauty students of SMK Negeri 3 Payakumbuh. The number of samples is 60 people from KC1 and KC2. The type of data is primary data and secondary data. Data collection techniques use questionnaire sheets in class XI TataKecantikan. Instrument testing uses validity and reliability tests. Data analysis techniques include descriptive statistical analysis, prerequisite tests such as normality and linearity tests, and hypothesis testing using Pearson product-moment correlation. Based on the results of data analysis, the learning motivation variable obtained a value of 51.67% in the good category. The research results for the entrepreneurial interest variable achieved an average score of 41.67% in the good category. The results of the self-confidence indicator obtained a value of 48.33% in the good category. Based on the research results, there is a linear relationship between the learning motivation variable and the entrepreneurial interest variable, with a significant deviation from linearity value of 0.875 > 0.05, with a perfect correlation degree of 0.879. It is recommended that schools use the research results as a reference to enhance students' learning motivation and interest in entrepreneurship.